2016
DOI: 10.1177/2331216516640486
|View full text |Cite
|
Sign up to set email alerts
|

Preferred Compression Speed for Speech and Music and Its Relationship to Sensitivity to Temporal Fine Structure

Abstract: Multichannel amplitude compression is widely used in hearing aids. The preferred compression speed varies across individuals. Moore (2008) suggested that reduced sensitivity to temporal fine structure (TFS) may be associated with preference for slow compression. This idea was tested using a simulated hearing aid. It was also assessed whether preferences for compression speed depend on the type of stimulus: speech or music. Twenty-two hearing-impaired subjects were tested, and the stimulated hearing aid was fit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 67 publications
6
42
0
Order By: Relevance
“…These listeners achieved thresholds between 427 and 854 Hz on the TFS-AF test. These findings are consistent with and extend the observation of Moore and Sek (2016) that six of their older HI listeners could not complete the TFS-LF test but were able to complete the TFS-AF test.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…These listeners achieved thresholds between 427 and 854 Hz on the TFS-AF test. These findings are consistent with and extend the observation of Moore and Sek (2016) that six of their older HI listeners could not complete the TFS-LF test but were able to complete the TFS-AF test.…”
Section: Resultssupporting
confidence: 91%
“…Indeed, associations between speech-in-noise identification and TFS sensitivity have been reported (Hopkins and Moore 2011;Neher et al 2012), and these occur even when confounding effects of age, hearing loss, and cognition are controlled for (Füllgrabe, Moore, and Stone 2015;Oberfeld and Klöckner-Nowotny 2016). In addition, it has been argued that sensitivity to TFS information might determine which signal-processing features in hearing aids (such as slow versus fast dynamic range compression) would be more beneficial for a HI listener (Moore 2008;Moore and Sek 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, these results do not clearly support (or arguably contradict) either a processing efficiency, general temporal processing, or auditory-only based explanation of the link between speech recognition and TFS. To our knowledge, no previous study has investigated whether signal processing strategy affects the relation between TFS sensitivity and speech in noise recognition, however, Moore and Se R k (2016) reported that older adults with poorer TFS sensitivity are more likely to prefer slow compression than those with better sensitivity to TFS. In this study, we did not collect data on subjective preferences for signal processing strategies, but it would interesting for future research to further investigate the relation between subjective and objective outcome measures.…”
Section: The Relation Of Tfs To Aided Speech Recognitionmentioning
confidence: 97%
“…Perez et al (2014) therefore suggest that testing TFS sensitivity prior to hearing aid fitting could provide useful information in terms of predicting, and managing individuals' expectations of, hearing aid outcomes. Further support for the idea that information regarding TFS sensitivity should be considered prior to hearing aid fitting is provided by Moore and Se R k (2016) who found that participants with poorer sensitivity to TFS showed a tendency to prefer slow compression over fast compression (although there was a lot of variation between individuals) and Lopez-Poveda et al (2017), who found that temporal processing ability predicted aided speech intelligibility in noise in adults with hearing impairment.…”
Section: Tfs and Hearing Impairmentmentioning
confidence: 99%
“…One problem with the TFS-LF test is that some subjects are completely unable to perform the test using the selected test frequency (often 500 Hz). A variation on the test that can be performed by most subjects is the TFS-AF test [55,56]. This is similar to the TFS-LF test except that ' is fixed (usually at 180 ) and the frequency is adaptively varied to determine the threshold.…”
Section: Sensitivity To Temporal Fine Structure (Tfs)mentioning
confidence: 99%